2011
DOI: 10.1038/oby.2010.106
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral Bone Marrow Fat Is Positively Associated With Visceral Fat and Inversely Associated With IGF‐1 in Obese Women

Abstract: Recent studies have demonstrated an important physiologic link between bone and fat. Bone and fat cells arise from the same mesenchymal precursor cell within bone marrow, capable of differentiation into adipocytes or osteoblasts. Increased BMI appears to protect against osteoporosis. However, recent studies have suggested detrimental effects of visceral fat on bone health. Increased visceral fat may also be associated with decreased growth hormone (GH) and insulin-like growth factor 1 (IGF-1) levels which are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
230
7
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 294 publications
(266 citation statements)
references
References 34 publications
22
230
7
7
Order By: Relevance
“…Using 1H-MRS we have found increased bone marrow fat in premenopausal women with high visceral fat compared to women with low visceral fat despite normal BMD. In addition, visceral fat correlated with vertebral bone marrow fat, but there was no association between bone marrow fat and body mass index (BMI), subcutaneous or total abdominal fat depots [18]. This suggests distinct metabolic roles for visceral and subcutaneous fat.…”
mentioning
confidence: 82%
“…Using 1H-MRS we have found increased bone marrow fat in premenopausal women with high visceral fat compared to women with low visceral fat despite normal BMD. In addition, visceral fat correlated with vertebral bone marrow fat, but there was no association between bone marrow fat and body mass index (BMI), subcutaneous or total abdominal fat depots [18]. This suggests distinct metabolic roles for visceral and subcutaneous fat.…”
mentioning
confidence: 82%
“…High body mass index (BMI) is associated with various diseases, including cardiovascular, obstructive sleep apnea, diabetes mellitus type 2, specific types of cancer and osteoarthritis (2). Bone metabolism is also abnormal in obesity (3) and positive and negative factors have been identified to be associated with bone health status (4)(5)(6). A number of previous studies have revealed that obesity stimulates bone formation by inhibiting apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that individuals with higher BMI are more likely to suffer hyperinsulinemia, as impaired production of insulin-like growth factor-1 (IGF-1)-binding globulins results in increased expression of IGF-1, which stimulates the differentiation of osteoblasts and promotes bone formation. 13 It should be noted that body weight and BMI also reflect the nutritional status of humans, and malnutrition directly affects bone reconstruction. 14 Johnson et al, Kim et al and Wu SF and Du XJ also demonstrated positive correlation of body mass index and BMD in their study.…”
Section: Discussionmentioning
confidence: 99%